Justiça percebida, emoções e satisfação em episódios de reclamação. - Nunesmaia, Ananda Lia Santana (2009)
In order to identify factors that lead to consumer satisfaction, concern with episodes of complaints has emerged, contemporary studies about complaints have provided evidence that the concept of justice is a fundamental basis for understanding the complaint process and its results from the consumers point of view. Allied to the study of justice perceptions, also emerge the concern with the emotions of the claimants, that has key role in influencing customer satisfaction and behavioral intentions. In this context, this dissertation aims examining the relationship between perceived justice, emotions, and (dis)satisfaction in episodes of complaints. For its scope has been taken basis authors like Dos Santos (2001), Tax, Brown and Chandrashekaran (1998), Smith and Bolton (2002) and Shoefer and Ennew (2005) and was also carried out a descriptive cross-sectional study using a sample of three hundred people, consisting of people who have had negative situations in episodes of complaints. Overall, the results confirmed all the hypotheses from the theoretical model. More specifically, the results indicate that, during episodes of complaint, the perceptions of distributive justice, procedural and interactional influence emotions and consumer satisfaction. With the exception of "fear", "shame" and "guilt" all other emotions are influenced by at least one perception of justice. The procedural justice influences three emotions (anger, contempt, negative surprise), interactional justice also affects three emotions (joy, anger, positive surprise), and finally, the distributive justice influences five emotions (interest, disgust, distress, positive surprise and negative surprise). For the interviewees, despite the employees not being rude, treat them with courtesy and be nice, and the companies, in some cases, do not obstruct their access and listen to customer complaints they still do not have positive attitudes towards fulfilling the complaint fully and satisfactorily.